Encapsulation of the antioxidant ascorbyl palmitate in V-type granular cold-water swelling starch affects the properties of both. (1st June 2017) - Dries, D.M.; Knaepen, L.; Goderis, B.; Delcour, J.A.
Highlights: Granular cold-water swelling starch (GCWSS) (excessively) forms lumps in water. Ascorbyl palmitate was encapsulated in GCWSS. Doing so beneficially affected its dispersibility in water. Swelling power decreased when degree of complexation increased. Encapsulated ascorbyl palmitate still had substantial antioxidant capacity. Abstract: This study reports on the functionality of V-type crystalline granular cold-water swelling starch (GCWSS) in complex with lipid (functionalized) molecules. Maize and potato GCWSS contain (empty) single helical amylose (AM) crystals which can serve as lipid complexing matrices. Different concentrations of ascorbyl palmitate (AscP) were inserted in the hydrophobic cavities of the GCWSS AM helices by a low temperature infusion method. Volumetric particle size distributions of the ensuing products in water were determined using laser light scattering. Upon contact with water, the parent maize GCWSS formed lumps more than did the parent potato GCWSS. It is hypothesized that variations in the spatial distribution of cold-water soluble V-type crystals are at the origin of this difference. In contrast, GCWSS-AscP inclusion complexes formed homogenous dispersions in water. Furthermore, the impact of inclusion complex formation on cold-water swelling properties was investigated. The close packing concentration increased and the swelling power and carbohydrate leaching decreased when the level of encapsulated AscP increased. Finally, in a Trolox equivalent antioxidant capacity test, encapsulated AscP still had up to 70% of the antioxidant capacity of free AscP.